Islam in South Korea: progress and challenges of da’wah activities since the 1950s - Mohd Ghazi, Ahmad Faris Naqiyuddin; Fathil, Fauziah (IIUM Press, 2017)
This book aims to introduce Islam and Muslims in South Korea to non-Korean readers of history, especially given the increasing popularity of Korean culture, particularly in the music and entertainment industries. This study therefore provides insights into the existence of the Muslim community in South Korea, something that is unknown to many and also on the challenges and problems facing both Korean and foreign Muslims in South Korea. It has been more than half a century since the end of the Korean War in 1953 when Islam first established its foothold in South Korea, yet to date only about 0.02% of its population is Muslim (about 45,000 South Korean Muslims) while the number of foreign Muslims continue to increase, reaching about 200,000 in number. Using a qualitative approach and interviews with Korean Muslim individuals, this study provides information on how Islamic da’wah was carried out in South Korea, the factors contributing to the spread of Islam, and challenges facing the da’i in performing da’wah. Moreover, this study also provides information on several Muslim countries, Muslim organisations and the individuals involved in da’wah activities in South Korea, especially with regard to their efforts and contributions. Finally, this study highlights the prospects of Islam in the country and presents several suggestions on modern ways of carrying out da’wah in 21st century South Korea.